Pengaruh Social Media Marketing dan Electronic Word of Mouth Terhadap Keputusan Pembelian melalui Brand Image pada Point Coffee Bandung - Valencia Sahanaya; Putu Nina Madiawati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Technological developments cannot be separated from the influence of the internet which has now integrated into people's daily lives, many companies are utilizing technology, especially social media in their main business strategy to reach a larger target audience in marketing their products. The purpose of this research was to determine the influence of Social Media Marketing and Electronic Word of Mouth on Purchase Decisions through Brand Image at Point Coffee Bandung. The method used is a quantitative method with descriptive analysis and Structural Equation Modeling (SEM) analysis method through SmartPLS 3.0 software. The results obtained in this study are that Social Media Marketing variables affect Purchase Decisions, Electronic Word of Mouth influences Purchase Decisions, Social Media Marketing variables affect Brand Image, Electronic Word of influences Brand Image, Social Media variables affect Purchase Decisions through Brand Image, Electronic Word of effect on Purchasing Decisions through Brand Image.